FALB: a FC protocol link aggregation algorithm - Zhaohui WANG; Jianliang SHEN; Xia ZHANG; Ting CHEN (Dianxin kexue)
Link aggregation is a common technology to increase the bandwidth by bundling multiple physical links into a logical link.However, in a switching network based on the fibre channel (FC) protocol, as the forwarding traffic continues to concentrate, traditional static link aggregation algorithms have problems of poor load balance and low reliability.A dynamic load balancing link aggregation algorithm flow adaptive load balancing (FALB) based on FC protocol messages was proposed, which could realize dynamic adaptive matching of traffic and a reconnection protection mechanism for broken links.The results show that compared with the static load balancing algorithm design, the algorithm mechanism could maintain the effective bandwidth ratio above 95%, effectively improving the load balancing characteristics and reliability of the aggregated link.